2009
DOI: 10.1258/td.2008.080241
|View full text |Cite
|
Sign up to set email alerts
|

Acalculous cholecystitis in a patient with Plasmodium falciparum infection after a trip to the Dominican Republic

Abstract: Acalculous cholecystitis has been associated with several infectious agents, but its relation with Plasmodium falciparum infection has not been clearly defined. This is the first case of acalculous cholecystitis produced by Plasmodium falciparum infection that is directly documented and should be included among the differential diagnoses of acalculous cholecystitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…A MEDLINE search showed that only 10 cases of malarial AAC have been reported in the literature. [19][20][21][22][23][24][25][26][27] Table 1 describes the clinical characteristics of the reported cases of malarial AAC, including our case. The paucity of cases is possibly due to under-reporting, since the symptoms and signs (e.g., abdominal pain and tenderness) of AAC are nonspecific.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A MEDLINE search showed that only 10 cases of malarial AAC have been reported in the literature. [19][20][21][22][23][24][25][26][27] Table 1 describes the clinical characteristics of the reported cases of malarial AAC, including our case. The paucity of cases is possibly due to under-reporting, since the symptoms and signs (e.g., abdominal pain and tenderness) of AAC are nonspecific.…”
Section: Discussionmentioning
confidence: 99%
“…All cases of malarial AAC, including ours, showed two or more of these criteria. [19][20][21][22][23][24][25][26][27] Although AAC is classically associated with a high rate of life-threatening complications (e.g., gangrene and perforation), such complications have not been described with malarial AAC (Table 1). Despite this observation, an increased risk of gallbladder gangrene and perforation in patients with malarial AAC cannot be convincingly ruled out.…”
Section: Discussionmentioning
confidence: 99%